Health care and poor relief in Protestant Europe, 1500-1700 - Cunningham, Andrew, Dr; Grell, Ole Peter (Studies in the social history of medicine., 1997)
This book provides an outline of the developments in health care and poor relief in Northern Europe by drawing on research into local conditions and mapping general patterns of development.